2020
DOI: 10.1177/1468087420967873
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ammonia and hydrogen as CO2-free fuels for heavy duty engines using a high pressure dual fuel combustion process

Abstract: This work is a numerical study of the use of ammonia and hydrogen in a high-pressure-dual-fuel (HPDF) combustion. The main fuels (hydrogen and ammonia) are direct injected and ignited by a small amount of direct injected pilot fuel. The fuels are injected using a dual fuel injector from Woodward L’Orange, which can induce two fuels independently at high pressures up to 1800 bar for the pilot fuel and maximum 500 bar for the main. The numerical CFD-model gets validated for of hydrogen-HPDF with experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 22 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…electricity and advanced biofuels), hydrogen has the potential to address some of the key emission reduction challenges when combined with ICE technologies. In particular, the H 2 fuelled ICE (H2ICE) is the only alternative keeping the ICE powerplant that does not produce any tank-to-wheel CO 2 emissions at the tailpipe (as well as IC engines fed with ammonia, 14 however more suitable for ship applications). Contrarily to FC powertrain systems, H2 ICEs can be fuelled with non-purified hydrogen, resulting in significantly lower production cost of hydrogen fuel.…”
Section: Introductionmentioning
confidence: 99%
“…electricity and advanced biofuels), hydrogen has the potential to address some of the key emission reduction challenges when combined with ICE technologies. In particular, the H 2 fuelled ICE (H2ICE) is the only alternative keeping the ICE powerplant that does not produce any tank-to-wheel CO 2 emissions at the tailpipe (as well as IC engines fed with ammonia, 14 however more suitable for ship applications). Contrarily to FC powertrain systems, H2 ICEs can be fuelled with non-purified hydrogen, resulting in significantly lower production cost of hydrogen fuel.…”
Section: Introductionmentioning
confidence: 99%
“…This increases the relative impact of unburned CH 4 emissions on climate change. 8 To demonstrate this adverse effect, Stettler et al 9 analysed the energy consumption, GHG emissions and pollutants from five after-market dual-fuel engine configurations in two vehicle platforms. They reported that over a transient cycle, lean-burn NG fuelled vehicles reduced CO 2 emissions by up to 9% when compared to the diesel-only baseline.…”
Section: Introductionmentioning
confidence: 99%
“…10 This approach has been tried and tested with homogeneous mixtures, [11][12][13][14][15] and has also proven to work with direct injection of the gaseous fuel into the cylinder. 16,17 Although the concept of high-pressure gas injection above 300 bar is very recent, 18 direct gas injection has been used for both marine [19][20][21][22] and heavy-duty 8,23 applications. Another approach is to use a glow-plug to create a local high temperature zone inside the combustion chamber.…”
Section: Introductionmentioning
confidence: 99%